SANKSI DUDUAK BASIGHIAH DI JORONG CENDRAWASIH NAGARI TIGO JANGKO KECAMATAN LINTAU BUO - Nurvala Nurvala; Yustiloviani Yustiloviani (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
Sanctions for duduak basighiah in Jorong Cendrawasih for people who do not carry out this tradition, are prevented from getting married, are not allowed to live in the Jorong, are not allowed to carry out walimah ursy, the family is banished by the niniak mamak. Then, thus the importance of this tradition is carried out to establish family intimacy and strengthen the relationship between the male and female families. The basighiah duduak tradition is carried out before the marriage contract at the women's house by holding alek sakampuang for the sighiah shreds process. This procession is a form of notification to the village community that a girl is getting married. Islamic law review of the tradition of basighiah duduak is a habit that has lived in the midst of society. This custom is classified as urf fasid because it contains disadvantages from the provisions of the basighiah basighiah tradition of sanctions, this sanction applies to couples who are getting married if they do not carry out the basighiah sitting tradition.